STUDENTS' OPINIONS ABOUT MOBILE LEARNING - Iscioglu, Ersun; Rasteh, Sina (Iated-Int Assoc Technology Education A& Development, 2013)
Developing information and communication technology closely affects every aspect of our lives. Similarly, new technologies and methods make a change in educational environments. Especially, smartphones and PDA's accelerate the use of different approaches in learning environments. It is anticipated that mobile learning will start to take an important place in the sense that it provides students with the opportunity of being involved in learning-teaching environments whenever and wherever they want. In other words, with the flexibility it provides, mobile learning will be included in educational environments for the sake of not only students but also institutions and instructors. Consequently, it is possible that mobile learning will turn into being one of the most important environments of distance education. In this sense, it is quite important that mobile learning and similar practices should be assessed according to students' opinions. Students' opinions are very important for new educational applications. Especially it is important for develop more effective and richer learning environment. The purpose of this study is to analyses opinions of graduate students' for Mobile Learning, specifically in terms of expectations and effectiveness. This study is designed as qualitative research. For this purpose focus group interviews and open-ended questions are conducted as data collection method. The participants of the research consist of 38 master students who registered ITEC542 IT and Instruction course at 2012-2013 Spring Semester. Data gathered as a result of the study was analyzed with descriptive analyses. At the end of the study, it was determined that the expectations of the students on mobile learning and their opinions about the activity are affirmative.
5th International Conference on Education and New Learning Technologies (EDULEARN) -- JUL 01-03, 2013 -- Barcelona, SPAIN
Keywords: Mobile Learning (M-learning); Students opinions; Distance Education